UTILIZATION OF FAMILY MEDICINE PLANTS IN TREATMENT OF BREAST INFECTION AND FEMALE GENITAL ORGANS IN KEKERI VILLAGE, GUNUNGSARI DISTRICT, WEST LOMBOK IN WEST NUSA TENGGARA - I Gusti Agung Ayu Hari Triandini (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2019)
Breast and female genital organs infections are sensitive health problems for women. By knowing family medicine plants, the role of family as primary health care will be more optimal. The Kekeri villager is rarely using their land to be made a pharmacy area plants. This might be due to their lack of knowledge about family medicine plants in terms of their utilization. The purpose of this research is to investigate it as well as to introduce the types of family medicine plants and their usage. This is an observational descriptive research with cross sectional study with quota sampling technique questionnaire (50 respondents) then continued with editing, coding, tabulating, data processing. The results showed that the majority of respondents (52%) did not utilize family medicine plants in the treatment of breast and female organ infections. 40% of respondents are already know the benefits of family medicine plants. Generally, the Kekeri villager only maintains the medicinal plants which at the same time can become a menu for daily foods. Types of medicinal plants that are mostly grown and efficacious in the care of breast and female genital organs are Lannea coromandelica, Sesbania grandiflora, Alpinia galanga, Moringa oleifera, Muntingia calabura, Sauropus androgynus, Anredera cordifolia, Piper betle, Zingiber officinale and Curcuma domestica. As the treatment of breast infection, the raw materials are boiled, eaten / drunk and applied topically. While for the treatment of female genital organs, the raw materials are usually used as immersion water when bathing or consumed as herbal medicine.